(untitled) (Zaporizhzhia Historical Review, 2021)
On the article ìMilitary fitness of the Red cavalry and Cossacks heritageî the author considers the fact that in 1930-ies the Soviet Union paid the main attention to the ideological propaganda but not to the professional training of soldiers. Because of the reason the Cossackís experience was not employed, and the training of the Red cavalry was worse than of Cossack one.